Pengembangan LKS Berbentuk Komik Materi Program Linear Berbasis Penemuan Terbimbing Siswa Kelas XI SMK Wisnuwardhana Malang - Oktavianus Bumma; Nia Wahyu Damayanti; Muhammad Baidawi (Journal of Education and Learning Mathematics Research (JELMaR), 2020)
Learning tools are one important aspect to determine the success of a learning design. Student worksheet is one of the learning tools. The purpose of this study is as follows. 1) to find out how to develop a mathematics learning worksheet in the form of comics based on guided discovery on linear program material, 2) to find out the validity and practicality of a mathematics learning worksheet in the form of comics based on guided discovery on linear program material. In this research the method used is the development method. So the research explained that what was developed was a comic-based worksheet based on guided findings on linear program metrics. The subjects in this study were students of class XI Vocational School Wisnuwardhana Malang. Based on the LKS development research results that have been obtained that the validity results assessed by three validator experts are 1) material expert validator, 2) media expert validator, and 3) linguist validator reaches a percentage of 72.20%. In this criterion, the worksheets that were developed were good (valid) and the results of practicality were obtained from the student questionnaire responses and obtained an average value of 3.3 which in this criterion was declared good (practical). From the development of LKS in the form of comics based on guided discoveries on linear program material, it was concluded that the development of LKS is valid and practical so that it is suitable to be used in mathematics learning.